Validation of an Integrative Methodology to Assess and Monitor Reductive Dechlorination of Chlorinated Ethenes in Contaminated Aquifers - Tarnawski, Sonia-Estelle; Rossi, Pierre; Brennerova, Maria V.; Stavelova, Monika; Holliger, Christof (Frontiers in Environmental Science, 2016)
Bioremediation of tetra-and trichloroethene-contaminated aquifers is frequently hampered due to incomplete dechlorination to the more toxic dichloroethene (DCE) and vinyl chloride (VC), indicating insufficient knowledge about the biological mechanisms related to aquifer functioning. A methodology based on the joint analysis of geochemical and microbiological datasets was developed to assess the presence of the biochemical potential for complete reductive dechlorination to harmless ethene and to explain the reasons for which degradation often stalls at the more toxic intermediates. This methodology is composed of three successive steps, with i) the acquisition of geochemical data including chlorinated ethenes, ii) the detailed analysis of the bacterial community structures as well as the biochemical potential for complete dechlorination using microcosms and molecular detection of organohalide-respiring bacteria and key reductive dehalogenases, and iii) a statistical Multiple Factor Analysis combining the above mentioned abiotic and biotic variables in a functional modelling of the contaminated aquifer. The methodology was validated by analyzing two chlorinated ethenes-contaminated sites. Results from the first site showed that the full biochemical potential for ethene production was present in situ. However, redox potential was overall too high and locally manganese reduction out-competed chlorinated ethenes reduction, explaining the reasons for the local accumulation of DCE and VC to a lesser extent. The second contaminated aquifer was under bioremediation by successive cheese whey injections. Analysis demonstrated that cheese whey additions led to increasingly reduced redox conditions and that hampered reductive dechlorination was not due to competition with other anaerobic respiration processes. Complete reductive dechlorination to ethene was preferentially occurring under methanogenic conditions. DCE and VC accumulation was probably induced first by low pH resulting from whey fermentation and at a later stage by phosphate limitation. In conclusions, the proposed methodology successfully allowed the identification of biogeochemical processes limiting or supporting complete dechlorination in both aquifers. The integrative approach provided fundamental information about the functional heterogeneity of the contaminated aquifers in time and space, and can be used as a reliable tool to support corrective decision-making in the development of remediation strategies based on natural attenuation of chlorinated ethenes.